The Valuations of the Near Polygon G_n - De Bruyn, Bart (The Electronic Journal of Combinatorics, 2009)
We show that every valuation of the near 2n-gon G_n, n ≥ 2, is induced by a unique classical valuation of the dual polar space DH(2n-1,4) into which G_n is isometrically embeddable.